2022
DOI: 10.3389/fpsyg.2022.942048
|View full text |Cite
|
Sign up to set email alerts
|

Firm innovation activities and consumer brand loyalty: A path to business sustainability in Asia

Abstract: BackgroundIn recent years, technological advancements have increased the importance of innovation activities. Therefore, firms invest millions of dollars in innovation activities to ensure long-term business sustainability. Similarly, consumer concerns have increased dramatically over the past years. Thus, brand loyalty has become a top priority for firms and consumers. In this background, this research examines how firms’ innovation activities translate into consumer brand loyalty to assure business sustainab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 100 publications
0
5
0
Order By: Relevance
“…A normality test ensures that the collected data is suitable for multivariate analysis, thereby maintaining the validity and reliability of the data (Yi & Safeer, 2022). The effective questionnaire sample size was 550, with 137, 138, 150, and 125 questionnaires from freshmen, sophomores, juniors, and seniors, respectively.…”
Section: Findings and Discussion Normality Test And Descriptive Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…A normality test ensures that the collected data is suitable for multivariate analysis, thereby maintaining the validity and reliability of the data (Yi & Safeer, 2022). The effective questionnaire sample size was 550, with 137, 138, 150, and 125 questionnaires from freshmen, sophomores, juniors, and seniors, respectively.…”
Section: Findings and Discussion Normality Test And Descriptive Analysismentioning
confidence: 99%
“…Since a company's reputation largely depends on customer satisfaction, enhancing customer satisfaction will positively impact the company's long-term development (Khan et al, 2022). A study examining the satisfaction of 100 microfinance bank customers found that company image positively impacts customer satisfaction and loyalty (Hayati et al, 2020).…”
Section: Competence In Improving Customer Satisfactionmentioning
confidence: 99%
“…51 Yi et al suggest that firms' innovation efforts on processes, products, and physical environment, positively related the brand prototype, thereby leading to brand preference, brand recommendation, and brand loyalty. 53 Past studies suggested that the problem of brand aging also warrants attention, as it needs to be effectively addressed as part of the long-term operation and management of brands, eg Keller. 54 Some admired brands, such Harley-Davidson and Mountain Dew, maintain leading positions in their respective industries.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Fourth, it has led to a situation where the long-term customer relationship is the means to ensure sustainability. Therefore, brand loyalty has emerged as an important area for marketers to ensure the long-term survival of the business organization [140]. The hotel practitioners have the responsibility of framing long-term strategies to promote brand loyalty among customers.…”
Section: Managerial Implicationsmentioning
confidence: 99%